2011
DOI: 10.1891/0889-8391.25.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Substance Use, and Their Co-Occurrence: Advances in Clinical Science

Abstract: Research and clinical literatures are replete with examples that psychological disorders are related to drug use, abuse, and dependence. The preponderance of scientific work addressing relations among psychopathological processes and drug use, abuse, and dependence has been focused primarily on psychotic disorders, major depression, antisocial personality disorder, and attention deficit hyperactivity disorder. This corpus of empirical work has indicated that there are clinically meaningful relations among part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Most research addressing relationships between self-management processes and substance use has focused primarily on psychotic disorders, antisocial personality disorder, and mood disorders (Zvolensky, Buckner, Norton, & Smits, 2011). However, research has also indicated that self-management processes are negatively related to the consumption of nicotine, alcohol and other drugs (Connolly, Noel, & Mezo, 2017;Foxx & Axelroth, 1983;Khantzian, 1990).…”
Section: Self-managementmentioning
confidence: 99%
“…Most research addressing relationships between self-management processes and substance use has focused primarily on psychotic disorders, antisocial personality disorder, and mood disorders (Zvolensky, Buckner, Norton, & Smits, 2011). However, research has also indicated that self-management processes are negatively related to the consumption of nicotine, alcohol and other drugs (Connolly, Noel, & Mezo, 2017;Foxx & Axelroth, 1983;Khantzian, 1990).…”
Section: Self-managementmentioning
confidence: 99%
“…Simply put, it may be understood in terms of the processes that guide the setting and achievement of goals (46). Most research addressing relationships between self-management processes and substance use has focused primarily on psychotic disorders, antisocial personality disorder, and mood disorders (47). However, research has also indicated that self-management processes are negatively related to the consumption of nicotine, alcohol and other drugs (48; 49).…”
Section: Self-managementmentioning
confidence: 99%
“…Although there has been a long-standing recognition that anxiety psychopathology and substance use disorders often cooccur, scienti fi c attention devoted to understanding the underlying nature of these relations has been limited (Zvolensky, Buckner, Norton, & Smits, 2011 ) . This gap in knowledge is unfortunate, as there are (a) high prevalence rates of anxiety and substance use disorders among treatment-seeking as well as the general population; and (b) relations between these conditions are important to their onset, maintenance, and course.…”
Section: Complexities In Assessment Of Personality and Behavioral Dismentioning
confidence: 99%